Pattern of Stroke among Adult (A-MMD) and Childhood Onset (C-MMD) Moyamoya Disease (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Though relatively rare, moyamoya disease (MMD) may have varied presentation in different age group. Different stroke types are major presentation of this enigmatic disease. Objective: The aim of this study was to compare the stroke subtypes among adult (A-MMD) and childhood onset (C-MMD) patients with Moyamoya disease (MMD).Methodology: This was a hospital based observational study, conducted in the department of Neurology, Dhaka Medical College Hospital, Bangabandhu Sheikh Mujib Medical University and National Institute of Neurosciences and Hospital, Dhaka, Bangladesh in between July, 2007 to June, 2016. Sample size included 36 children and 14 adult patients of MMD presenting with either ischemic or hemorrhagic stroke, within one month of the index event.Result: Majority of participants were below 10 years of age with a mean age at onset of 16.56(±10.6) years. There was a female predominance. Patients younger than 20 years, presented mostly with ischemic stroke (32 versus 4 patients); whereas those above 20 years of age presented mostly with hemorrhagic stroke (6 versus 8 patients). The difference was statistically significant (p value = 0.006). Large artery infarct (15) and hemodynamic infarct (17) were common among patients in children; whereas intracerebral hemorrhage (dICH, lICH, IVH among 3, 4 and 1 patients respectively) was frequent (8) among the adult (p value = 0.006).Conclusion: While different pattern of ischemic stroke is common among children with MMD, the adults present mostly with hemorrhagic stroke subtypes.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 87-90